Procreation and population in historical social science - Danna, Daniela, 1967- (Anthem Press, 2021)
The book sees procreation, the forgotten basis of population dynamics, and its macrohistorical results through the lenses of world-system analysis. This interdisciplinary book sheds light on the historical paths leading to the current unprecedented numbers of humans on the globe, fuelled by the capitalist demand for labor.